MicroRNA-106a targets autophagy and enhances sensitivity of lung cancer cells to Src inhibitors. (May 2017) - Rothschild, Sacha I.; Gautschi, Oliver; Batliner, Jasmin; Gugger, Mathias; Fey, Martin F.; Tschan, Mario P.
Highlights: Src inhibition results in autophagy activation in NSCLC cell lines. Combining Src with autophagy inhibition results in significant cell death. Induction of ULK1 upon Scr inhibition allows for autophagy activation. Src inhibition causes induction of the ULK1 targeting microRNA-106a. Expression of the "oncogenic" miR-106a sensitizes NSCLC cells to Src inhibition. Abstract: Objectives: Src tyrosine kinase inhibitors (TKIs) significantly inhibit cell migration and invasion in lung cancer cell lines with minor cytotoxic effects. In clinical trials, however, they show modest activity in combination with chemotherapeutic agents. Possible resistance mechanisms include the induction of cytoprotective autophagy upon Src inhibition. Autophagy is a cellular recycling process that allows cell survival in response to a variety of stress stimuli including responses to various treatments. Material and methods: We screened autophagic activity in A549, H460, and H1299 NSCLC cell lines treated with two different Src-TKIs (saracatinib, dasatinib) or shRNA targeting SRC . The autophagy response was determined by LC3B-I to −II conversion, increased ULK1 epxression and increased GFP-LC3B dot formation. Autophagy was inhibited by pharmacological (bafilomycin A, chloroquine) or genetic ( ULK1 shRNA) means. Expression of miR-106a and miR-20b was analyzed by qPCR, and we used different lentivral vectors for ectopic expression of either miR-106a mimetics, anti-sense miR-106a or different miR-106a-363 cluster constructs. Results: In the current study we found that Src-TKIs induce autophagy in lung adenocarcinoma cell lines and that a combination of autophagy and Src tyrosine kinase inhibition results in cell death. Moreover, Src-TKI induced autophagy depends on the induction of the key autophagy kinase ULK1. This ULK1 upregulation is caused by downregulation of the ULK1 -targeting microRNA-106a. An inverse correlation of miR-106a and ULK1 expression was seen in lung adenocarcinoma. Accordingly, ectopic expression of miR-106a in combination with Src-TKI treatment resulted in significant cell death as compared to control transduced cells. Conclusions: Autophagy protects lung adenocarcinoma cells from Src-TKIs via a newly identified miR-106a- ULK1 signaling pathway. The combined inhibition of Src and ULK1 /autophagy might represent a promising treatment option for future clinical trials. Lastly, our data might challenge the term "oncogenic" miR-106a as it can promote sensitivity to Src-TKIs thereby underlining the context-dependent function of miRNAs.